Adding chitosan nanoparticles of green tea extract in diluent and thawing temperatures ameliorate the post-thawed quality of Boer buck semen - Suherni Susilowati; Imam Mustofa; Tri Wahyu Suparyogi; Adeyinka Oye Akintunde; Djoko Agus Purwanto; Wurlina Wurlina; Suzanita Utama; Sri Mulyati (Asian Pacific Journal of Reproduction)
Objective: To improve the quality of post-thawing Boer buck semen for artificial insemination by adding green tea extract chitosan nanoparticles to skimmed egg yolk diluent, and the proper thawing temperature. Methods: The ejaculate of Boer buck was added to skimmed egg yolk diluent without (the control group) and with adding 1 μg of chitosan nanoparticles of green tea extract per mL of diluent (the treatment group). Then, the diluted semen was filled in French mini straws containing 60× 106 live sperm per straw, frozen in a standard protocol, and stored as frozen semen at -196 °C for a week. Six replicates from each group were diluted for 30 s at 37 °C or 39 °C sterile water to evaluate the semen quality. Results: Post-thawing (at 37 °C or 39 °C) of live sperm, progressive motility, and plasma membrane integrity were lower compared to those of the pre-freezing stage (P<0.05). Thawing at 37 °C resulted in no significant difference in live sperm, progressive motility, and plasma membrane between the control group and the treatment group (P>0.05). The live sperm, progressive motility, and plasma membrane of the treatment group in the pre-freezing stage, and post-thawed at 39 C were higher compared to those of the control group (P<0.05). There was no significant difference in malondialdehyde (MDA) concentration, DNA fragmentation, and catalase concentration of thawing at 37 °C compared to those of 39 °C in the same group. The MDA concentration and DNA fragmentation in thawing at 37 °C and 39 °C of the treatment group were significantly lower than those of the control group (P<0.05). However, the catalase concentration in thawing at 37 °C and 39 °C of the treatment group was not significantly different than the control group (P>0.05). Conclusions: Higher quality post-thawing Boer buck semen is achieved by adding 1 μg/mL of chitosan nanoparticles of green tea extract to the skimmed egg yolk diluent and thawing at 39 °C.